Incidence of infection after early intramedullary nailing of open tibial shaft fractures stabilized with pinless external fixators - Kulshrestha, Vikas (Medknow Publications, 2008)
BACKGROUND: A major drawback of conventional fixator system is the penetration of fixator pins into the medullary canal. The pins create a direct link between the medullary cavity and outer environment, leading to higher infection rates on conversion to intramedullary nailing. This disadvantage is overcome by the AO pinless fixator, in which the trocar points are clamped onto the outer cortex without penetrating it. This study was designed to evaluate the role of AO pinless fixators in primary stabilization of open diaphyseal tibial fractures that received staged treatment because of delayed presentation or poor general condition. We also analyzed the rate of infection on early conversion to intramedullary nail. MATERIALS AND METHODS: This study is a retrospective review of 30 open diaphyseal fractures of tibia, which were managed with primary stabilization with pinless fixator and early exchange nailing. Outcome was evaluated in terms of fracture union and rate of residual infection. The data were compared with that available in the literature. RESULTS: All the cases were followed up for a period of 2 years. The study includes Gustilo type 1 (n=10), 14 Gustilo type 2 (n=14), and type3 (n=6) cases. 6 cases (20%) had clamp site infection, 2 cases (6.7%) had deep infection, and in 28 cases (93%) the fracture healed and consolidated well. CONCLUSION: This study has highlighted the valuable role of pinless external fixator in the management of open tibial fractures in terms of safety and ease of application as well as the advantage of early conversion to intramedullary implant without the risk of deep infection.